Zonal character of the flora of kurgans in central and southern Ukraine - Sudnik-Wójcikowska, Barbara; Moysiyenko, Ivan (Biodiversity: Research and Conservation, 2011)
In the years 2004-2010 floristic studies were carried out on kurgans in 4 different climatic/vegetation zones: 3 steppe zones (west and central Pontic desert steppe, west Pontic grass steppe, west and central Pontic herb-rich grass-steppe) and a forest steppe zone. Among the 450 kurgans surveyed, 106 barrows met the selection criteria. The species composition and the contribution of different life forms to the flora of kurgans changed along the north-south gradient. Jaccard's similarity coefficient and Wards clustering method were used to compare the qualitative composition of flora in particular zones. The results of this comparison confirmed floristic differences between kurgans located in the four zones. Kurgans in the desert steppe zone proved to have the most distinct flora among the floras considered. The biggest similarities were found between the flora of kurgans in the forest steppe zone and that of barrows in the west and central Pontic herb rich grass steppe.